(3HhGYK GdacQI aj MhGOK GdgLQIs - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s ((3fLe GdOjf YeH Hf eMeO Hf agO GdgGTei s)
(3ChdgG (B:s
(3MOKfG SjOfG hehdGfG GdTjN GdGeGe bGd CNHQfG GdTjN GdEeGe GdYdGeI GdMGaX eaJi GdaQb HbjI GdeLJgOjf CHh TGeI QMeI Gddg Ydjg bQGAI Ydjg s
(3BNQgG (B:s
(3hcGfg eG cGf Shi GdfbT GdeaJOi Ydi YJHI GdHGH jQi aGLRd Gddg GdCLQ hGdKhGH def jeMh gPG GdfbT ef GdHGH dGf eMhg hGLH dHWdGfg s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdJGQjNs